2014
DOI: 10.1186/1745-9974-10-2
|View full text |Cite
|
Sign up to set email alerts
|

A real – life observational pilot study to evaluate the effects of two-week treatment with montelukast in patients with chronic cough

Abstract: BackgroundDifferent conditions make the proximal airways susceptible to tussigenic stimuli in the chronic cough (CC) syndrome. Leukotrienes can be implicated in the inflammatory mechanism at play in it. Montelukast is a selective cysteinyl-leukotriene receptor antagonist with proven effectiveness in patients with asthma. The aim of our real-life pilot study was to use montelukast to relieve cough symptoms in patients with CC allegedly due to the two frequent causes other than asthma – upper airway cough syndro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 32 publications
1
9
0
1
Order By: Relevance
“…Our study is similar to the work of Philip G et al, where marked improvement was observed in nasal and ocular symptoms after the two weeks treatment with montelukast 10 mg, the same study also concluded that this significant reduction in the symptoms of AR imposed a positive impact on asthma-related problems of the patient who were dealing with both the disorders. 14 Montelukast particularly has a positive impact on cough and all the discomforts associated with it, 15 and this is quite evident in our patients as well.…”
Section: Discussionsupporting
confidence: 63%
“…Our study is similar to the work of Philip G et al, where marked improvement was observed in nasal and ocular symptoms after the two weeks treatment with montelukast 10 mg, the same study also concluded that this significant reduction in the symptoms of AR imposed a positive impact on asthma-related problems of the patient who were dealing with both the disorders. 14 Montelukast particularly has a positive impact on cough and all the discomforts associated with it, 15 and this is quite evident in our patients as well.…”
Section: Discussionsupporting
confidence: 63%
“…One prospective observational study reported that montelukast therapy for 2 weeks significantly improved symptoms of chronic cough. 31 However, the possibility of natural remission cannot be ruled out in an observational study lacking a control group. LTRAs were not effective in a RCT of 276 patients with subacute post-infectious cough, suggesting the lack of direct anti-tussive effects of LTRAs.…”
Section: Empirical Treatment For Non-specific Chronic Coughmentioning
confidence: 99%
“…Compared with individuals with no health-related dysfunction, it revealed that cough was associated with dysfunction in patients usual daily activities, particularly in the categories of ambulation, social interaction, sleep and rest, work, home management, and recreation [16]. According to a study done by Mincheva et al, in 2014, found that patients with chronic cough due to upper airway cough syndrome or gastroesophageal reflux disease but not asthma reported significant relief of their symptoms after 2 weeks of treatment with Montelukast [17].…”
Section: Discussionmentioning
confidence: 99%